Evaluating adolescent and adult athletes with congenital heart disease - Abela, M. (Cardiology Practice, 2021)
Improved cardiovascular care of patients with congenital heart disease has led to a significantly improved survival in this previously high-risk population. More patients are keen to engage in regular physical activity, some even opting for competitive sports. The beneficial effects of exercise are well known, though balancing this benefit with the possible risks in these patients is at times difficult. The lack of evidence about the optimal exercise regime in these patients along with the perceived risk of complications and disease progression has often propelled physicians to take a more conservative approach. A sedentary lifestyle is however having repercussions in this growing population. Exercise is safe in most patients with congenital heart disease. Surveillance will help to identify higher-risk individuals. The aim of this document is to provide recommendations (level of evidence C), using a five-step strategy.